Gamma-beam generation at the synchrotron "Pakhra" by resonance excitation of accelerated electrons - Bashmakov, Yu.A.; Karpov, V.A. (Вопросы атомной науки и техники, 2012)
System of homogeneous extraction of gamma-beam from the 1.2 GeV electron synchrotron "Pakhra" is discussed. Accelerated electrons are slowly brought to the tungsten target, which is placed inside the synchrotron vacuum chamber. During extraction high frequency voltage on accelerator’s cavity is hold constant. Limited electron betatron oscillations are exiting by means of the gradient and the octupole pole face windings. Time uniformity of gamma quanta flow is provided by a special choice of the time dependence of the index of the synchrotron guide magnetic field. Control of the extraction process by a computer with usage of a feedback circuit will be performed. Обсуждается система однородного во времени вывода гамма-пучка из электронного синхротрона "Пахра" на энергию 1,2 ГэВ. Ускоренные электроны медленно направляются на вольфрамовую мишень, которая размещена внутри вакуумной камеры синхротрона. Во время вывода высокочастотное напряжение на ускоряющем резонаторе поддерживается постоянным. Ограниченные бетатронные колебания электронов возбуждаются посредством градиентной и октупольной полюсных обмоток. Однородность потока гамма-квантов во времени обеспечивается специальным выбором зависимости от времени показателя спада ведущего магнитного поля синхротрона. Для эффективного управления процессом вывода может быть использована цепь обратной связи. Обговорюється система однорідного у часі виведення гамма-пучка з електронного синхротрона "Пахра" на енергію 1,2 ГеВ. Прискорені електрони повільно спрямовуються на вольфрамову мішень, яка розміщена всередині вакуумної камери синхротрона. Під час виведення високочастотна напруга на прискорюючем резонаторі підтримується постійною. Обмежені бетатронні коливання електронів збуджуються за допомогою градієнтної і октупольної полюсних обмоток. Однорідність потоку гамма-квантів в часі забезпечується спеціальним вибором залежно від часу показника спаду провідного магнітного поля синхротрона. Для ефективного управління процесом виведення може бути використаний ланцюг зворотного зв'язку.